1998
DOI: 10.1016/s0925-4773(97)00187-1
|View full text |Cite
|
Sign up to set email alerts
|

Orphan nuclear receptor RORα-deficient mice display the cerebellar defects of staggerer

Abstract: It has recently been shown that the neurological mutant mouse staggerer (sg) harbors a deletion within the Rora gene that encodes the orphan nuclear receptor ROR alpha. This deletion removes an exon encoding part of the ligand binding domain of the putative receptor, generating an ROR alpha truncated protein (ROR alpha(sg)). It is unknown whether sg acts as a null or highly hypomorphic allele. To address this question, we have generated a null mutation of Rora by targeted disruption of its DNA binding domain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 29 publications
7
131
0
Order By: Relevance
“…Their temporal expression patterns suggest they are more likely to be important in cerebellar development. The observed ROR␣ expression pattern at the different stages we examined was not surprising, since it was previously reported that this receptor plays a crucial role in the cerebellum development such as Purkinje cell differentiation and maturation (Dussault et al, 1998;Steinmayr et al, 1998;Gold et al, 2003). Except for ROR␣, the detailed expression pattern of COUP-TFI, COUP-TFII, GCNF, ERR␥, and LRH-1 in the cerebellum, however, was not known before this study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Their temporal expression patterns suggest they are more likely to be important in cerebellar development. The observed ROR␣ expression pattern at the different stages we examined was not surprising, since it was previously reported that this receptor plays a crucial role in the cerebellum development such as Purkinje cell differentiation and maturation (Dussault et al, 1998;Steinmayr et al, 1998;Gold et al, 2003). Except for ROR␣, the detailed expression pattern of COUP-TFI, COUP-TFII, GCNF, ERR␥, and LRH-1 in the cerebellum, however, was not known before this study.…”
Section: Discussionmentioning
confidence: 62%
“…Mice with staggerer were found to carry a deletion within the ROR␣ gene that blocks Purkinje cells differentiation, resulting in congenital ataxia and cerebellar hypoplasia (Sidman et al, 1962;Dussault et al, 1998), and ROR␣ knockout mice show phenotypes similar to those seen with staggerer mice (Dussault et al, 1998;Steinmayr et al, 1998;Gold et al, 2003). Given these phenotypes, we next systematically analyzed the ROR␣ expression pattern in the cerebellum during different developmental stages.…”
Section: The Expression Patterns Of Err␥ Ror␣ and Er␤ In The Develomentioning
confidence: 99%
“…The orphan receptor ROR␣ (31) is directly involved in regulating cerebellar development, as ROR␣-null (staggerer) mice display Purkinje cell depletion and cerebellar ataxia (74,77). In the cerebellum, both Hr (31) and VDR (78) are abundantly expressed in granule cells; therefore, in granule cells the presumed protein complex may influence cerebellar development and/or function.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Nurr1, a member of the Nurr1/Nur77/Nor1 subfamily of receptors, appears to be essential for the migration, differentiation, and survival of dopaminergic neurons of the ventral mesencephon (Zetterstrom et al, 1997;Saucedo-Cardenas et al, 1998;Le et al, 1999;Wallen et al, 1999). Similarly, the orphan nuclear receptor RORα is crucial for maturation and survival of Purkinje cells in the cerebellum (Dussault et al, 1998;Chu and Zingg, 1999;Vogel et al, 2000). Finally, the inhibitory orphan receptor, COUP-TFI, is known to mediate neocortex identity as suggested by the loss of regional organization and specific gene expression in the absence of COUP-TFI function (Zhou et al, 2001).…”
Section: Orphan Nuclear Receptors In Cns Developmentmentioning
confidence: 99%